Application Progress of Bear Bile Powder and Ursodeoxycholic Acid in Liver Disease and its Mechanism of Action. (June 2020) - Zhao, Xin; Wang, Ruipeng; Cao, Zhengmin; Liu, Shuang
Abstract: Liver disease is a type of disease that threatens human life and health, including viral liver disease, cirrhosis, fatty liver, liver cancer and other liver diseases. Slowing or even blocking the progress of liver disease has great clinical significance. Today, western medicine lacks effective treatment for liver diseases, and Chinese medicine has achieved significant results in the treatment of liver diseases. This article reviews the application progress of ursin bile powder and ursodeoxycholic acid in liver disease, and hopes to advance the mechanism of ursin bile powder and ursodeoxycholic acid in the treatment of liver disease, which will help its clinical application and new drug development.